Erratum to McEwen et al. "Diurnal changes and levels of fibrin generation are not altered by continuous positive airway pressure (CPAP) in obstructive sleep apnoea (OSA). A randomised, placebo-controlled crossover study" (Thromb Haemost 2012; 108: 701–709) (Thrombosis and Haemostasis, 2013)
In the original article by McEwen BJ, Phillips CL, et al. "Diurnal changes and levels of fibrin generation are not altered by continuous positive airway pressure (CPAP) in obstructive sleep apnoea (OSA). A randomised, placebo-controlled crossover study. (Thromb Haemost 2012; 108: 701–709) the authors recently realised that a statistical analysis error has resulted in minor data errors in Table 1. They also realised that no data on the Epworth Sleepiness Score (ESS) was listed despite the table legend listing the meaning of ESS.The correct (mean ± SD) baseline data are: AHI (events/h): 37.7 ± 24.4; ODI (events/h): 30.7 ± 22.6; SaO2-T90 (%TST): 5.9 ± 10.1; Min SaO2 (%) 79.3 ± 9.8; ESS 10.2 ± 4.9.The correct (mean ± SEM) CPAP vs Placebo CPAP data are: AHI (events/h): 5.7 ± 1.7 vs 40.2 ± 5.2, p<0.00001; ODI (Events/h): 4.2 ± 1.7 vs 39.6 ± 4.4, p<0.00001; SaO2-T90 (%TST): 0.6 ± 0.3 vs 9.8 ± 2.3, p<0.001; Min SaO2 (%) 90 ± 1.2 vs 79 ± 1.4, p<0.00001; Treatment Compliance (h/night) 4.3 ± 0.4 vs 3.4 ± 0.4, p<0.05; Epworth Sleepiness Score (ESS) 7.4 ± 0.8 vs 8.7 ± 0.7, p<0.05.Although this new data is very similar to the original data, the authors felt it important to correct. Importantly, these errors had no influence on the main coagulation outcomes and study interpretation.